GENDER ANALYSIS OF CHILD INVESTMENT AND CHILD QUALITY AMONG FARMER FAMILIES IN INDONESIA - Puspitawati, Herien; Sarma, Ma'mun; Elmanora, Elmanora; Azizah, Yasmin (Jurnal Ilmu Keluarga dan Konsumen, 2020)
Families have obligations to protect and care for their children. The general objective of this study was to analyze the gender of the investment and the quality of the children in highland farmers. The study was conducted at highland areas at Cianjur Regency (Sindangjaya Village, Cipanas Sub-district) and Bogor Regency (Petir Village, Dramaga Sub-district). The findings showed that they were 4 (four) indicators of child investment latent variable such as the allocation of time togetherness between parents and children, investment in education and health, material allocations, and protection of children. Moreover, there were 5 (five) indicators of child quality latent variable such as the physical quality, learning achievement, child’s behavior, psycho-social-spiritual, and the quality of life. The first result showed that there was no difference between boys and girls in total of child investment, but there was significantly difference between boys and girls in total of child quality. The second result proved that the latent variable of child investment has significantly positive effect on latent variable of child quality. As recommendation, the study need to be continued with various family characteristics and broadening analysis such as the effect of child investment and child quality to the child happiness.